The Effect of Pseudomonas aeruginosa Addition on 1,1,1-Trichloro-2,2-bis(4-chlorophenyl)ethane (DDT) Biodegradation by Brown-rot Fungus Fomitopsis pinicola - Atmira Sariwati; Adi Setyo Purnomo (Universitas Gadjah Mada, 2018)
Effect of addition of Pseudomonas aeruginosa on 1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane (DDT) biodegradation by Fomitopsis pinicola had been investigated. P. aeruginosa was added into F. pinicola culture at 1, 3, 5, 7 and 10 mL (1 mL ≈ 1.53 x 109 P. aeruginosa bacteria cells/mL culture). The addition of 10 mL of P. aeruginosa showed the highest DDT biodegradation approximately 68% during 7 days incubation in Potato Dextrose Broth (PDB) medium, which was higher than biodegradation of DDT by F. pinicola only (42%) at the same incubation time. 1,1-dichloro-2,2-bis(4-chlorophenyl)ethane (DDD), 1,1-dichloro-2,2-bis(4-chlorophenyl)ethylene (DDE) and 1-chloro-2,2-bis(4-chlorophenyl)ethylene (DDMU) were detected as metabolites from DDT biodegradation by mixed cultures of F. pinicola and P. aeruginosa.